Cyclophosphamide-Induced Gastric Histopathological Alterations in Golden Hamsters - Maysoon Elrashdy; Rima Benomran; Esraa Farag; Mustafa Meelad; Hend Al-derbash; Mona Al-Amery; Hamed Saleh; Abeer Amer (AlQalam Journal of Medical and Applied Sciences, 2025)
Cyclophosphamide is a widely used chemotherapeutic and immunosuppressive agent, but its gastric toxicity remains poorly characterized. This study investigated dose-dependent histopathological changes in the gastric mucosa of golden hamsters following cyclophosphamide administration. Twenty-seven adult female hamsters were divided into control and treatment groups. Animals received intraperitoneal doses of 100 or 200 mg/kg cyclophosphamide on alternating days for one week. Gastric tissues were harvested, fixed in formalin, processed by paraffin embedding, and stained with Hematoxylin and Eosin (H&E) and Periodic Acid-Schiff (PAS) for microscopic evaluation. Histological examination revealed progressive mucosal damage with increasing doses, ranging from mild epithelial alterations at 100 mg/kg to severe disruption, inflammatory infiltration, and reduced mucopolysaccharide secretion at 200 mg/kg. Cyclophosphamide induces dose-dependent gastric injury in golden hamsters, underscoring the importance of histological monitoring during therapy. The model provides a relevant preclinical platform for studying chemotherapy-induced gastric toxicity.